Rhabdomyosarcoma Diagnosis Expert System Applying Adaptive Neuro Fuzzy Inference System Method - Iringin Telaumbanua, Dian (Management of Information System Journal, 2024)
Rhabdomyosarcoma (RMS) is a cancer that originates from striated muscles (muscles that move the body). Is a cancer that is formed from the soft tissues in the body, such as muscles, fat cells, bones, joints and blood vessels. This cancer grows and develops in any part of the body and Rhabdomyosarcoma disease is most commonly found in children. To get an accurate diagnosis, it requires an expert system using the Adaptive Neuro Fuzzy Inference System (ANFIS) method. Rhabdomyosarcoma disease was designed using the Visual Basic Net 2008 programming language and using the MYSQL database, hoping that it could become an alternative tool and bring positive impacts for all its users.